Tax Justice Perceptions on Tax Compliance of WPOP on KPP Pratama Tampan Kota Pekanbaru - Estu, Ahmad Zulkarnain; Sella, Tommy; Irman, Mimelientesa; Anton; Eddy, Pujiono (First Ciera Publisher, 2023)
The main purpose of this research is to determine the effect of tax justice on tax compliance. Tax justice is the nature (action of treatment) that is not arbitrary or impartial to the applicable tax system. Determination of the sample using the Slovin method. Methods of data analysis are multiple linear regression with SPSS. Independent variables are general fairness, exchange with government, attitude toward taxation of the wealthy, preferred tax rate structure, and self-interest. The dependent variable is Tax Compliance. This research adduces that general justice, government reciprocity, tax rate structure, and personal interest have positive significant, while special provisions have no significant effect on tax compliance.